2010
DOI: 10.1080/10934520903388855
|View full text |Cite
|
Sign up to set email alerts
|

Heat-shock protein (Hsp70) and cytochrome P-450 (CYP1A) in the white mulletMugil curema(Pisces:Mugilidae) as biomarkers to assess environmental quality in coastal lagoons

Abstract: Biomarkers have been useful tools to monitor some effects of pollution in coastal environments. Hepatic expression of heat-shock protein 70 (Hsp70) and cytochrome P450 1A (CYP1A) were analyzed in white mullet (Mugil curema) by RT-PCR from July, 2005 until July, 2006 in three coastal lagoons located in the southern Gulf of California, Mexico. These three coastal systems receive contaminants derived from local anthropogenic activities. Heat-shock proteins function to maintain protein integrity in the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Elevated water temperature generally leads to an increase in expression levels of hsp genes in several fish (Arai et al, ; Ojima et al, ; Cui et al, ; Im and Ghil, ). Hsps also respond to various environmental stresses, such as heavy metals, pollution, and infection (Rios‐Sicairos et al, ; Roberts et al, ; Lapointe et al, ; Ribecco et al, ).…”
mentioning
confidence: 99%
“…Elevated water temperature generally leads to an increase in expression levels of hsp genes in several fish (Arai et al, ; Ojima et al, ; Cui et al, ; Im and Ghil, ). Hsps also respond to various environmental stresses, such as heavy metals, pollution, and infection (Rios‐Sicairos et al, ; Roberts et al, ; Lapointe et al, ; Ribecco et al, ).…”
mentioning
confidence: 99%
“…As mentioned before, HSP70 is a molecular chaperon that helps in maintaining conformity of many cellular proteins (Hartl and Martin 1995; Martin and Hartl 1997). In fact the expression of HSP70 remained high throughout the year in livers of fishes that live in water polluted with hydrocarbon (Rios‐Sicairos et al). This observation indicated that HSP70 was required for maintaining conformity of cytochrome P450 protein including EROD that might be required for detoxification of pollutants.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we investigated to test whether there is any relationship between the expression of heat shock protein70 (HSP70) and carbofuran‐ induced CYP1A1 because only few reports have indicated that HSP70 could be involved in the regulation of EROD (Ferraris et al 2002; Rajagopalan et al 2005; Rios‐Sicairos et al 2010). In our study, it has been observed that induction of CYP1A1 is associated with the increase of PKC and HSP70 and both have parallel dose dependent function with CF.…”
Section: Introductionmentioning
confidence: 99%